Model Pembelajaran Berbasis Proyek Pada Mata Kuliah Media Pembelajaran - Fajar Adinugraha (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of this research is to explain the forms of Learning Media subject with a Project-Based Learning models. In addition, to find out the description of student’s perception in the Project-Based Learning model in the Learning Media subject. The research also aims to find out student’s response to the lecturer’s teaching skill at using the Project-Based Learning model. It is a quantitative descriptive research that uses literature study and survey methods. One of Learning Media subject activities with the Project-Based Learning model is the creation of video tutorials with stages: 1) creating interactive power points using Microsoft Office Power Point application; 2) creating flash using iSpring free 7 application; 3) making a video tutorial using the Screecast-O-Matic application; and 4) making publication through social media Youtube. Student’s perception in the Project-Based Learning model in Learning Media subject is in the good category (very good 30% and good 70%). Next, student's response to the lecturer’s teaching skill at using the Project-Based Learning model is also in the good category (very good 50% and good 50%)